Developing Critical and Aesthetic Thinking in Future Art Teachers through Art Analysis - Esanova Lobar Kulmurotovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores methods for enhancing critical and aesthetic thinking in future art teachers through the analysis of visual art works. It discusses pedagogical strategies that combine reflective observation, interactive discussions, and project-based learning. The study emphasizes the role of integrating cognitive, emotional, and aesthetic dimensions to foster analytical, creative, and culturally informed thinking among students.